Chapter Afterword Reflections on a Post/Critical Peace Education - Kester, Kevin (Taylor & Francis, 2023)
This edited collection brings together a series of conceptual explorations and practical case studies to illuminate a developing innovative praxis of transdisciplinary peace and education. Drawing on the work of the Cambridge Peace and Education Research Group as well as international scholars, this book responds to calls for transdisciplinary peace and education praxis and presents innovative examples of peace and education research practices, peace interventions in educational settings, and alternative ontologies in peace and education work. Foregrounding the concept of 'second-order reflexivity', the book prioritises the lived experiences and viewpoints of struggling populations regarding the worth of 'peace' as grounded within their contexts. Ultimately, this book showcases how the practices of peace education and research can challenge the binaries of modern and postmodern approaches and provide examples of holistic transdisciplinary approaches that embrace complexity and criticality. Contributing new knowledge to peace and education, this volume will be of great interest to academics, post-graduate students and researchers in the field of peace education, peace studies and development studies.